Karrikadjurren - May, Sally K. (Abingdon)
1 online resource
Keywords: Presenting a story of art and artists in Gunbalanya, western Arnhem Land between the years 2001 and 2005, this book explores the artistic community surrounding the primary place of art creation and sale in the region, Injalak Arts, an art centre established in the remote Aboriginal community of Gunbalanya. Using a variety of disciplinary approaches including archaeological analysis and material culture studies, anthropology, historical research, oral histories, and reflexive ethnography, the social context of art creation is explored. May argues that Injalak Arts as a place activates and draws together particular social groupings to form a sense of identity and community. It is the nature of this community, or "Karrikadjurren" in the local dialect, that is the primary focus of this book, with the artworks painted during this period providing unique insights into art, identity, community, and innovation. This book will be of most interest to those working in or studying archaeology, material culture studies, museum studies, anthropology, sociology,Aboriginal studies, art history, Australian studies, rock art, and development studies. More specifically, this book will appeal to scholars with an interest in the archaeology or anthropology of art, ethnoarchaeology, and the nature and politics of community archaeology.